Malignancies in systemic lupus erythematosus: a 2015 update. Issue 5 (September 2015) - Goobie, Gillian C.; Bernatsky, Sasha; Ramsey-Goldman, Rosalind; Clarke, Ann E.
Abstract : Purpose of review: Patients with systemic lupus erythematosus (SLE) have altered incidences of certain malignancies as compared with the general population. This review summarizes the recent literature on risk of malignancy in SLE and proposed mechanisms for these altered susceptibilities. Recent findings: Recent studies have confirmed previous data showing an increased risk of non-Hodgkin's lymphoma, lung, liver, vulvar/vaginal, and thyroid malignancies, whereas demonstrating a decreased risk of breast and prostate cancer. Lymphomagenesis in SLE has been linked to increased activity of multiple inflammatory cytokines as well as possible viral diseases. The decreased rates of hormone-sensitive cancers, such as breast and prostate, are speculated to be related to the presence of lupus autoantibodies and downregulation of certain proteins in SLE. This knowledge has been utilized to investigate new therapeutic modalities for these malignancies. Summary: Recent data confirm previously reported altered malignancy rates in SLE. Most striking in recent years are publications further elucidating mechanisms underlying cancer development in SLE, and subsequent investigations of potential therapeutics modulating these pathways.